Perlindungan Hukum Terhadap Pendidik Pada UPT Satuan Pendidikan - Irfandi Irfandi (Phinisi Integration Review, 2020)
The purpose of this study are; 1) To find out the protection of teachers in carrying out professional tasks at the UPT 6 Wajo Vocational Education Unit after the enactment of Ministry of Education and Culture Decree Number 10 of 2017 as an effort to protect the teaching profession; 2) Describe the fulfillment of the rights of the teachers at the 6th Wajo State Vocational School Education Unit after the enactment of the Minister of Education and Culture Regulation No. 10 of 2017 concerning Protection for Educators and Education Personnel; 3) Analyzing the supporting factors and inhibiting factors in creating a culture and school climate in UPT State Vocational Education Unit 6 Wajo after the enactment of Minister of Education and Culture Decree No. 10 of 2017. This type of research is qualitative. Data collection techniques are done by interview, observation and documentation. While the data analysis techniques go through the stages of data reduction, data presentation and conclusions. The results of this study show that: 1) The protection of teachers in carrying out professional tasks is sufficient, it can be seen from the even distribution of teaching hours, complete teacher administration tools, giving awards for teachers who excel and sanctions for violations committed by teachers are flexible; 2) Fulfillment of teacher rights in professionalism programs has been going well, seen from the provision of wise leave and permits, appreciation of professional development is quite high, and encouragement to immediately become professional through educator certification; 3) Supporting Factors and Inhibiting Factors in Creating a Disciplined School Culture and Climate, seen from the commitment of the teacher and all components of the school to realize it as a driving factor. While the inhibiting factor is the lack of awareness in adhering to school rules.